Pengaruh Self Esteem dan Self Efficacy Terhadap Kualitas Audit (Studi Kasus Pada Inspektorat Kabupaten Bireun) - Neo Agustina; Dewi Kemala Sari; Mulia Andirfa (Akbis: Media Riset Akuntansi dan Bisnis, 2022)
In ithe igovernment isector, iit iis inecessary ito icarry iout ian iaudit ito iensure ithat ithe imanagement iof istate ifinances iis icarried iout iproperly, itransparancy iand iaccountably iin iaccordance iwith ithe iapplicable ilaws iand iregulations iand ito iavoid icorrupt ipractices ion istate iassets. iThis istudy iaims ito iexamine ithe ieffect iof iself-esteem iand iself-efficacy ion iaudit iquality iat ithe iInspectorate iof iBireuen iRegency. iThe idata iused iin ithis istudy iis iprimary idata ias imany ias i36 isamples iwith isaturated isampling itechnique ior icensus. iThe imethod iused ito ianalyze ithe iindependent ivariable iwith ithe idependent ivariable iis ithe imultiple ilinear iregression imethod iand ithe iclassical iassumption itest. iThe iresults iof ithe istudy ipartially iself-esteem ihad ino ieffect ion iaudit iquality iat ithe iBireuen iRegency iInspectorate, iself-efficacy ihad ino isignificant ieffect ion iaudit iquality iat ithe iBireuen iRegency iInspectorate. iSimultaneously ishows ithat iself-esteem iand iself-efficacy ihave ia isignificant ieffect ion iaudit iquality iat ithe iBireuen iRegency iInspectorate.